Advances in the study of core fucosylation in mammals - TIAN Yinping; YI Wen (浙江大学学报. 农业与生命科学版)
Glycosylation is a major posttranslational modification, which involves in the regulation of important physiological functions. Among them, core fucosylation is an α1, 6-linked fucose to N-glycans, which catalyzes by only one glycosyltransferase. This review will focus on core fucosylation in mammals and the related biological functions. Fucosyltransferase 8 (FUT8) is the sole enzyme responsible for this modification via the addition of L-fucose residue from guanosine diphosphate-β-L-fucose. The crystal structure of human FUT8 provided insight into both catalytic mechanism and substrate recognition. Currently, core fucosylation plays an important role in tumor progression, immune regulation and stem cell differentiation. Moreover, fucose analogues were either the metabolic substitutes or inhibitors of fucosylation. In conclusion, the specific labeling and automatic synthesis of core-fucosylated N-glycans will play an important role in its further study and clinical application.